Artes visuais e tecnologias digitais na formação continuada dos profissionais de ensino médio - Sangoi, Tânia Losekann (2006)
The present research is part of the line of Research Education and Arts of the Pos Graduation Program in Education. The objective of this study is to reflect Art theory practice, and the Continued Formation of teachers of Secondary School, having present the educative processuality in the teaching of Visual Arts face to Digital Technologies. The interest for the subject appeared through the perception of the inexistence of a work in Art and the Digital Technologies, explicit requirement of the contemporary education. In the search of a better agreement and understanding of the questions that involve the subject, the theoretical basis was marked out with the thought of Pierre Lévy (1993 and 1996), Diana Domingues (2003), Edmond Couchot (1998 and 2003), Luiz Paulo Leopoldo Mercado (1999), Suzete Venturelli (2004), Maria Beatriz de Medeiros (2005), Tânia Esperon Maria Porto (2003), Ana Luiza Ruschel Nunes (2004), Ana Mae Barbosa (2002), Lucimar Bello Frange (2002), Lucia Santaella (2002), and others mentioned in the body of the dissertation. The approach of the research is qualitative through a study of case. The instruments of data collection consisted of questionnaire and half-structuralized intervenes of the participant observation of the daily field, the documentary analysis, the portfolio and the practice of the digital technologies, forming a data set of which significant and rewarding information had emerged. The research was developed at the State School of Basic Education Margarida Lopes , at Gonçalves Ledo street number 565 Camobi Santa Maria/RS . They had been part of the same research, two teachers of Visual Arts, attend in this Light School. The importance of the update of a continuous formation was the object of the investigation with the citizens, therefore as a mediating agent of the contemporary educational process involved in a permanent process of participative investigation, reflexive and contextualized in Art Education. Through the reflection of the teaching of Art and the continued formation, specified in this case by means of digital technologies, it is possible to (re)concept, contextualizing subjects, methods and methodology face educative practices. Being in possession of the collected data we made the analysis with crossing information that made possible beyond some interpretations, mainly the motivation of a reflexive practice and the incorporation of the continued formation process to the Visual Arts teachers. Though out the research we perceived that the Visual Arts knowledge, in the contemporary context in the researched School has been worked by descontextualized form, stagnated in Modern Art. In this way we can infer that the reflections process inexisted by the misinformation of the knout edges of the Art and its history, therefore by the lack of the process of continued formation. The lack of this process and the search of actualization were tenuous occurring in the frequency in no specific courses and some readings. We conclude that the use of digital technology in the teaching of Art didn t happen. We infer that the way for new and possible changes of the teacher s look to their professional performance in the Visual Arts teaching is without doubt the search for continued formation realignmenting to new perspectives face Visual Arts and digital technology. We also infer that Educative Visual Arts practice were permanently developed in the shared process, having present the reflection in the action on the action and on the reflection from the teachers and the School s context giving the visibility to formative process in the perspective of the teaching of contemporary Art plugging to Digital Art and claiming others possibilities of presupposed and a process of creation in the continued formation of teachers.